Management Tips for Glaucoma - Asad Jamal Dar, Amjad Akram, Muhammad Shahid (Pakistan Journal of Ophthalmology, 2008)
This article highlighted practical tips for glaucoma management. These tips include dealing with the glaucoma suspect, history taking, general medical history, gonioscopy, visual fields, optic disc cupping, secondary glaucomas, normal tension glaucoma and of course raised intraocular pressure. Emphasis being on practical tips rather than being comprehensive on glaucoma.